Hubungan Antara Pemahaman Sila Keempat Pancasila dan Sikap Demokratis Mahasiswa : Analisis di Lingkungan Ppkn C 2022 Unimed - Pingky Monica Hasugian; Bella Ayu Anzalia; Friska Lorentina Purba; Halimah Halimah; Martua Felix Simanullang (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The Republic of Indonesia is a country that has various ethnic, cultural, racial, religious and linguistic diversity. This diversity is united by the existence of Pancasila. Pancasila is the basis of the Republic of Indonesia which was ratified on August 18 1945. Pancasila is the basis of the State, the result of culture and people's thinking which is used as a guideline for life in society, nation and state. Pancasila has noble values ​​which are reflected in the Pancasila principles. The results of the research show that students in the PPKN C 2022 Unimed environment have varying levels of understanding of the Fourth Principle of Pancasila. There may be variations in their knowledge and understanding of the values ​​contained in the Fourth Precept, such as human rights, social justice, equality, and unity. This research has important implications for the development of citizenship education within PPKN and Medan State University in general. Efforts to increase students' understanding of Pancasila values ​​can contribute to the formation of a more democratic and participatory attitude.